An Afucosylated Anti-CD32b Monoclonal Antibody Induced Platelet-Mediated Adverse Events in a Human Fcγ Receptor Transgenic Mouse Model and Its Potential Human Translatability. (23rd October 2021) - Wolf, Babette; Jeliazkova-Mecheva, Valentina; Del Rio-Espinola, Alberto; Boisclair, Julie; Walker, Dana; Cochin De Billy, Benjamin; Flaherty, Meghan; Flandre, Thierry
Abstract: To assess the safety and tolerability of NVS32b, a monoclonal, afucosylated, anti-CD32b (FCGR2B) antibody, we used a humanized transgenic (Tg) mouse model that expresses all human Fc gamma receptors (FCGRs) while lacking all mouse FCGRs. Prior to its use, we extensively characterized the model. We found expression of all human FCGRs in a pattern similar to humans with some exceptions, such as low CD32 expression on T cells (detected with the pan CD32 antibody but more notably with the CD32b-specific antibody), variation in the transgene copy number, integration of additional human genes, and overall higher expression of all FCGRs on myeloid cells compared to human. Unexpectedly, NVS32b induced severe acute generalized thrombosis in huFCGR mice upon iv dosing. Mechanistic evaluation on huFCGR and human platelets revealed distinct binding, activation, and aggregation driven by NVS32b in both species. In huFCGR mice, the anti-CD32b antibody NVS32b binds platelet CD32a via both Fc and/or complementarity determining region (CDR) causing their activation while in human, NVS32b binding requires platelet preactivation and interaction of platelet CD32a via the Fc portion and an unknown platelet epitope via the CDR portion of NVS32b. We deemed the huFCGR mice to be overpredictive of the NVS32b-associated human thrombotic risk.